Online Dating Apps: How a Man’s Attractiveness Rating Depends on His Level of Disclosure and Women’s Level of Loneliness - Janulevičiūtė, Miglė; Mikuličiūtė, Vita (Information & Media, 2024)
The link between self-disclosure and attractiveness is well-researched, yet studies often overlook the rater’s loneliness, a potentially vital aspect in this dynamic. The aim of this study is to examine how women evaluate a man’s social and physical attractiveness in dating app profiles based on disclosed personal information. Additionally, it explores the connection between women’s feelings of loneliness and their assessment of social attractiveness in this context. 90 students, aged from 19 to 26, participated in the study. Participants were randomly assigned to three groups. All groups were presented with the same two photographs of a man but differed in the amount and depth of information presented next to each one (high, optimal, and no exposure). The UCLA Loneliness Scale (version 3) was used to measure loneliness, and the Interpersonal Attractiveness Scale was used to measure attractiveness. The study discovered that women rated a man disclosing an optimal amount of information as more physically attractive than one sharing excessive details. There were no between-group differences in ratings of a man’s social attractiveness. Although social attractiveness ratings correlated negatively with women’s loneliness (r = -0.32), loneliness did not significantly influence social attractiveness ratings based on disclosure levels.
Keywords: self-disclosure; physical attraction; social attraction; loneliness